Non-restrictive Adjective Interpretation and Association with Focus (2005)
This paper investigates a relationship between the non-restrictive interpretation of attributive adjectives, known in French as an épithète de nature, and non-compositional theories of focus interpretation. It is shown that a non-restrictive interpretation, in French and in English, arises not as a result of inherent properties of the noun modified by the adjective, but from accommodation of a presupposition that elements denoted by the noun generally have the property denoted by the adjective.